(untitled) (Global Journal of Human-Social Science, 2012)
Carrier liability in Islamic law is investigated in the present work The liability systems are classified into four distinct systems system based on the proved fault system based on fault supposition system based on the supposition of responsibility and system of absolute or mere responsibility All above systems are observed in Islamic law and there are viewpoint differences among jurisprudents as well as lawyers in the subjectof carrier liability However the dominant idea is on the carrier liability i e the carrier is responsible and the only way to get rid of responsibility is to declare the damage cause and the loss cannot be related to the carrier Damage assessment in Islamic law is also investigated